Intellectual methods for evaluating the state of UAV channels. Ch. 5 - Kashkevich, Svitlana; Shaposhnikova, Olena; Saienko, Nataliia; Shevchenko, Viktoriia; Holeho, Nataliia; Zaloznyi, Taras (Technology Center PC, 2025)
In this section of the research, intellectual methods for assessing the state of unmanned aerial vehicle (UAV) channels are proposed. During the study, the authors: 1. Developed an intellectual method for assessing the state of UAV channels based on the application of fuzzy set theory and artificial neural networks, which, while being sufficiently simple, allows for obtaining highly accurate solutions. The distinctive features of the proposed method include: – simultaneous assessment of the UAV channel state based on multiple evaluation indicators (impulse response, frequency response, and bit error rate); – real-time continuous assessment of several channel state characteristics; – continuous assessment of multiple channel state characteristics in both the downlink and uplink channels; – obtaining channel state assessments for each indicator on separate layers of the neural network through the construction of membership functions; – following the assessment of individual channel characteristics by separate neural network layers, a generalized channel state assessment is formed at their output. 2. Proposed a methodology for identifying the state of UAV control and data transmission channels. The novelty of the proposed methodology lies in: – considering a corrective coefficient during calculations to account for the degree of uncertainty regarding the state of UAV channels; – adding a corrective coefficient to address data noise resulting from distortions in information about UAV channel states; – reducing computational costs when assessing the state of UAV channels; – enabling calculations with input data of various natures and units of measurement.
Keywords: artificial intelligence; heterogeneous data processing; control and data transmission channels; reliability; efficiency; https://doi.org/10.15587/978-617-8360-13-9.ch5